Respuesta :
Answer:
[tex]3x^{2} -17x-28=(x-7)(3x+4)[/tex]
Step-by-step explanation:
we have
[tex]3x^{2} -17x-28[/tex]
equate to zero
[tex]3x^{2} -17x-28=0[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]3x^{2} -17x=28[/tex]
Factor the leading coefficient
[tex]3(x^{2} -(17/3)x)=28[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex]3(x^{2} -(17/3)x+(289/36))=28+(289/12)[/tex]
[tex]3(x^{2} -(17/3)x+(289/36))=(625/12)[/tex]
[tex](x^{2} -(17/3)x+(289/36))=(625/36)[/tex]
Rewrite as perfect squares
[tex](x-(17/6))^{2}=(625/36)[/tex]
[tex](x-(17/6))=(+/-)(25/6)[/tex]
[tex]x=(17/6)(+/-)(25/6)[/tex]
[tex]x=(17/6)(+)(25/6)=42/6=21/3[/tex]
[tex]x=(17/6)(-)(25/6)=-8/6=-4/3[/tex]
so
[tex]3x^{2} -17x-28=3(x-(21/3))(x+(4/3))[/tex]
[tex]3x^{2} -17x-28=(1/3)(3x-21)(3x+4)[/tex]
[tex]3x^{2} -17x-28=(x-7)(3x+4)[/tex]